What physicians want to learn about sickness certification: analyses of questionnaire data from 4019 physicians - Alexanderson Kristina; Hagberg Jan; Löfgren Anna (BMC, 2010)
Abstract Background Sickness absence is a problem in many Western countries. Physicians have an essential role in sickness certification of patients, which is often recommended in health care but may have side effects. Despite the potentially harming impact of sickness absence, physicians have very limited training in insurance medicine, and there is little research on sickness certification practices. Our aim was to ascertain what knowledge and skills physicians in different clinical settings feel they need in order to improve their competence in sickness certification. Methods The data for analysis were collected in 2004 in Stockholm and Östergötland Counties, Sweden, by use of a comprehensive questionnaire about sickness certification issues, which was sent to 7,665 physicians aged ≤ 64 years. The response rate was 71% (n = 5455). Analyses of association and factor analysis were applied to the various aspects of competence to establish a skills index and a knowledge index, which were used to compare the results for physicians in different clinical settings. Results Most physicians stated they needed more knowledge and skills in handling sickness certification, e.g. regarding how to assess work capacity (44%) and optimal length and degree of sickness absence (50%), and information about aspects of the social insurance system (43-63%). Few (20%) reported needing to know more about issuing sickness certificates. The index scores varied substantially between different clinical settings, and this disparity remained after adjustment for sex, years in practice, workplace policy, and support from management. Scores on the skills index were significantly higher for physicians in primary care than for those working in other areas. Conclusions A majority of physicians in most types of clinics/practices, not only primary care, indicated the need for more knowledge and skills in handling sickness certification cases. Increased knowledge and skills are needed in order to protect both the health and equity of patients. However, few physicians stated that they needed more skills in filling out sickness certificates, which contradicts previous findings about such documents being of poor quality and suggests that factors other than mere knowledge and skills are involved.